Digital Engineering Measures Correlated to Digital Engineering Lessons Learned from Systems Engineering Transformation Pilot. Issue 1 (12th April 2022) - Blackburn, Mark R.; McDermott, Tom; Kruse, Benjamin; Dzielski, John; Hagedorn, Tom
ABSTRACT: This paper discusses analysis that correlates Digital Engineering Success Measure (DESM) categories with lessons learned benefits observed during the NAVAIR Surrogate Pilot that applied Digital Engineering (DE) methods and tools using an Authoritative Source of Truth by modeling everything to demonstrate the art‐of‐the‐possible. The analysis correlated rating from seventeen lesson learned categories to 22 DESMs grouped into four metrics categories.